Pulmonary Alveolar Cell Carcinoma Revisited - Bovornkitti, Somchai (Asian Medical Journal and Alternative Medicine, 2022)
A healthy looking 75-year-old man sought a consultation with the author, a retired chest physician, following the man’s annual health examination, the report of which indicated that he had lung cancer. The author took him to a chest physician who carried out a series of investigations and diagnosed him as a case of pulmonary adenocarcinoma of the right lung. Thereafter, the patient received a full course of chemotherapy. Routine follow-up examinations of the case showed practically unchanged lesions over time and, apart from some psychological effects connected with knowing that he had cancer, the patient remained in normal health. The patient had been informed by the author at the time of his first consultation that he was actually a case of pulmonary alveolar cell carcinoma, which the author had reported in a paper 61 years ago.